Enhancing Community Well-Being in Sungai Ambawang District through PT. Graha Agro Nusantara's CSR Implementation - Lu'lua, Lu'lua; Suyatno, Adi; Kurniati*, Dewi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
Corporate Social Responsibility (CSR) constitutes a commitment by corporations or the business sector to enhance the economy through a focus on fulfilling social responsibilities, stressing the equilibrium among societal, economic, and ecological dimensions. This study aims to determine the implementation of PT Graha Agro Nusantara's CSR and the influence of CSR on the level of community welfare. This research was conducted in Muara Baru Village, Sungai Raya District, Kubu Raya District. The selection of research sites was done purposively (purposive). The selection of the sample used in this study was carried out by simple random sampling, amounting to 44 people. This research uses SPSS analysis with chi-square test. The results of this study indicate that the implementation carried out by PT Graha Agro Nusantara is good and there is an influence on the welfare of the community with social, economic and environmental indicators by looking at the increase in opinion in the community. Keywords: Implementation; Corporate Sosial Responsibility; Influence; Income; Public Welfare